Narcissists (Incorporated): A Reply to Morris - Anderson, Charles C. (Canadian Journal of Counselling and Psychotherapy, 2012)
It is usually assumed that the human condition can be improved in at least two ways; by developing an individual's potential for behaviour that is both prosocial and personally satisfying, and by bringing about social changes which might be expected to lead to the same goal. The two major industrialized nations havechosen one, but not the other, of the two paths. It is argued that the Human Potential Movement is preferred in the North American continent because itdoes not endanger the power by means of which the ruling élites manipulate the beliefs, values and self-concepts of the common run of men.